Design Studios: Approach to Achieve Smart Learning Environment (SLE) - Dr. Anamika Jiwane; Arch. Fariel Khan (International Journal of Engineering and Management Research, 2020)
Smart Learning Environment (SLE) is the hourly need to satisfy the urge generated by the new knowledge society. This includes a focus on learning methods to yield a required blend of learning environment that supports experience of effective and engaged learning. The essence of ‘SLE’ is to create a condition that can enhance the learners’ personalized and adaptive learning experience. For the Architecture and Design students, Studio- a physical space that allows students to accomplish their design learning in an innovative and creative manner, plays an integral role in their learning. The main objective of the paper is to redefine the concept of ‘Smart Learning Environment’ in the context of Design education and suggest a model for the ‘Smart Design Studio’ based on the perception of learners. The methodology includes surveys and group discussion at the University of Bahrain (UoB), to receive opinions on smart teaching-learning spaces and methods. A short experimental study was done to measure the impact on the design learning as a result of modifications done in the Design Studio. The experiment was centered on the theory of ‘Identity Development’ and ‘Personalization of spaces’. Finally, the paper concludes a new vision on SLE as a learner-centered-environment that allows multiple ways of learning to support all-round development of the learners. As a recommendation, authors suggest a model for the Design Studio to achieve effective, engaged and efficient learning. The key elements of the model are the disseminator and recipient of knowledge, learning methods, modes, tools and resources.